Phenotypic and molecular characterisation of novel Vicia faba germplasm with tolerance to acetohydroxyacid synthase‐inhibiting herbicides (AHAS) developed through mutagenesis techniques. Issue 10 (3rd April 2019) - Mao, Dili; Michelmore, Simon; Paull, Jeff; Preston, Christopher; Sutton, Tim; Oldach, Klaus; Yang, Shi Y; McMurray, Larn
Abstract: BACKGROUND: Faba bean ( Vicia faba L.) is an important crop in Australian farming systems, however, weed control is a major constraint due to a lack of in‐crop broadleaf herbicide options. To address this, we developed acetohydroxyacid synthase (AHAS) inhibitor herbicide tolerance in faba bean using mutagenesis techniques. Dose–response experiments, agronomic field evaluation and DNA sequencing of the AHAS gene were used to quantify and validate tolerance traits. RESULTS: Four M2 faba bean single‐plant biotypes (IMI‐1, IMI‐2, IMI‐3 and IMI‐4) at a frequency of 3.63 × 10 −6 were successfully recovered. Molecular characterisation of the AHAS gene identified two known target site mutations (resulting in protein substitutions Ala205Val and Ser653Asn) conferring tolerance. Phenotypic characterisation found that both mutations conferred high levels of tolerance to the imidazolinone herbicide imazapyr. However, although the Ala205Val substitution showed improved levels of cross‐tolerance to a range of sulfonylurea chemistries, the Ser653Asn substitution did not. In the field, IMI‐3 showed the highest level of agronomic tolerance across a range of imidazolinone herbicides. CONCLUSIONS: Mutagenesis techniques were successful in the development of tolerance to AHAS inhibitor herbicides in faba bean, and could facilitate the first safe in‐crop broadleaf herbicide control option in Australian faba bean production. © 2019 Society of Chemical Industry Abstract : High levels of target site tolerance could facilitate the first safe in‐crop herbicide option to control broadleaf weed species in Australian faba bean production.